KOMUNIKASI INTERPERSONAL DAN DAKWAH KOMUNIKASI DALAM ORGANISASI - Sahdani Harahap; Defrinal; Nining Yusmei (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2024)
Interpersonal communication as da'wah communication between communicators and communicants, is considered the most effective type of communication in terms of efforts to change a person's attitude, opinion, or behaviour. One of the most obvious features of organisational communication is the concept of relationships. Organisation as a network of interdependent relationships. If things are interdependent, this means that they influence and are influenced by each other. Communication satisfaction carries a relationship with job satisfaction, job satisfaction is a person's response to the various work environments he or she faces, such as co-workers, policies, promotions etc. The importance of a supportive climate in organisational communication is more emphasised to get job satisfaction. The leader as a responsible person in the organisation can contribute in generating a good communication climate in the organisation.